Tingkat Pemahaman Siswa Dalam Pembelajaran Geografi Secara Daring Di SMA Negeri 6 Kota Bengkulu - Muhammad Alfi; Dihamri Dihamri (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2022)
The Covid-19 pandemic has changed the face of education in Indonesia, which seems to have to implement an online learning system and from home. This condition will certainly require adaptation for students to understand the material to be taught. This is because the interaction process carried out by students and teachers is only carried out online. The purpose of this study was to analyze the level of understanding of students in online geography learning at SMAN 6 Bengkulu City. This type of research is descriptive and qualitative, the method used in this study is a survey. The data collection technique was carried out by using multiple choice questionnaires. The sample in this study was 130 students of class X. The data in the study were then processed with descriptive statistics and percentages. The results showed that the level of understanding of students in online learning at SMAN 6 Bengkulu City was in the "Pretty Good" category.